Advances in gene therapy technologies to treat retinitis pigmentosa - Petrs-Silva H (Dove Medical Press, 2013)
Hilda Petrs-Silva, Rafael LindenInstitute of Biophysics, Federal University of Rio de Janeiro, Rio de Janeiro, BrazilAbstract: Retinitis pigmentosa (RP) is a class of diseases that leads to progressive degeneration of the retina. Experimental approaches to gene therapy for the treatment of inherited retinal dystrophies have advanced in recent years, inclusive of the safe delivery of genes to the human retina. This review is focused on the development of gene therapy for RP using recombinant adenoassociated viral vectors, which show a positive safety record and have so far been successful in several clinical trials for congenital retinal disease. Gene therapy for RP is under development in a variety of animal models, and the results raise expectations of future clinical application. Nonetheless, the translation of such strategies to the bedside requires further understanding of the mutations and mechanisms that cause visual defects, as well as thorough examination of potential adverse effects. Keywords: retinitis pigmentosa, photoreceptor, gene therapy, AAV